Ultimate Ownership and Adjustment Speed Toward Target Capital Structures: Evidence from China. Issue 8 (2nd August 2016) - Zhou, Ting; Xie, Jun
ABSTRACT: We investigate whether ultimate ownership affects firms' adjustment speed toward target capital structures for Chinese publicly listed companies over the period 1999–2009. We divide our sample into state-owned enterprises (SOEs) and non-SOEs according to their ultimate ownership. We find that SOEs have higher leverage ratios and slower adjustment speeds toward target capital structures. Our results are consistent with the trade-off theory, implying that the political resources of SOEs can lead to a higher persistence and slower leverage adjustment speeds in comparison to non-SOEs. Finally, our results also raise a question: Why do Chinese companies adjust their capital structure so fast?